Analisis Penggunaan Tanaman Vetiver terhadap Stabilitas Lereng pada Bendungan Way Sekampung - Sari, Renanda Okta; Zain, Alfath; Pratiwi, Dian (Universitas Batanghari Jambi, 2024)
Problems that occur in the western part of As Way Sekampung have the potential for landslides to occur. Efforts used to handle slope strengthening by planting vetiver plants. The research method used to analyze slopes uses the limit equilibrium method on slip surface sections using the Morgenstren-Price method with the help of Geostudio 2023.1.0 software. SLOPE/W to get the safety factor under normal conditions and under seismic load conditions. By using a seismic load with a return period of 500 years (PE 10% in 50 years) with a Peak Ground Acceleration (PGA) value for the Way Sekampung Dam inundation area of 0,265 g. In vetiver plants, the root depth is simulated according to the top soil depth of 0,0 – 0,1 m. Soil planted with vetiver plants experienced an increase in the value of cohesion (c) by 74,42% and a decrease in the value of the angle of internal friction (φ˚) by 49,40%. The conclusion obtained was that slope stability in normal existing conditions was 4,525 and in normal vetiver plant strengthening conditions the safety factor increased to 4,529. Then, in the existing seismic conditions, the safety factor is 2,624 and in strengthening vetiver plants with seismic loads, the safety factor value increases to 2,626. It can be concluded that vetiver plants are able to strengthen slope conditions.